Modelling spreading process of a wildfire in heterogeneous orography, fuel distribution and environmental conditions - a complex networks approach - Perestrelo, Sara (2020)
Forest fires are phenomena that represent a great danger for the population and have severe environmental consequences. The greatest efforts in regard to direct confrontation require a large investment in terms of both financial and human resources, partly due to the unpredictability of fire behaviour and the fuel distribution that feeds its growth and spread. To deal with this unpredictability in a more efficient manner, our work focuses around the establishment of an optimal fire-break structure whose purpose is to block the spread along the landscape, at a minimal cost. It’s a preventative approach, which acts as a complement to direct confrontation and contributes to the reduction of material, economic and human losses. For the establishment of this optimal fire-break structure it is necessary to model fire spreading process and, for that, we use the multilayer network model, within the area of complex networks. We aim the construction of a network of networks that allows us to simulate the fire spreading process both at a local scale and at a more global scale.